Repurposing global agricultural support - Glauber, Joseph W.; Laborde Debucquet, David (American Enterprise Institute, 2022)
Countries around the world provide billions of dollars every year for agricultural support, with most of the benefits accruing to middle- and high-income farmers. Critics of agricultural subsidies may prefer a total global rollback, but this is widely believed to be politically untenable. In response, many have proposed repurposing subsidies to serve climate and nutrition goals. Repurposing subsidies to focus on either nutrition or climate change may positively affect one or both objectives, but the overall effects are surprisingly small and can involve outcomes that benefit one objective at the expense of the other.